A decision support system for software technology selection. (15th May 2018) - Farshidi, Siamak; Jansen, Slinger; de Jong, Rolf; Brinkkemper, Sjaak
Abstract: Software producing organisations face the challenge of including new technology in their products, such as cloud technologies and database management systems. As software architects and senior developers are not experts in this domain, they need to consult external experts or acquire the knowledge themselves. Software production, therefore, is a suitable domain to deploy decision support systems, that intelligently support these decision-makers in selecting the desirable technology for their product. We present a decision support system that supports decision-makers in choosing the most suitable database technology. The case studies and experts confirm that the approach increases insight into the selection process, provides a richer prioritised option list than if they had done their research independently, besides reduces the time and cost of the decision-making process.